Weigh Forward: a clinical audit of weight management in Australian general practice. Issue 3 (June 2016) - Hemmes, R. A.; Adam, N.; Dixon, J. B.
Summary: Weigh Forward was a prospective clinical audit, aimed to assess the use and efficacy of 12‐week weight management program in general practice. Twenty‐eight practitioners participated in the audit, with a total of 258 patients observed. Of these, 147 (57%) were retained to 24 weeks. Practices were asked to implement a structured 12‐week weight loss program, and encouraged to utilize relevant weight management guidelines as necessary. Patients were followed up regularly, and comprehensively assessed at baseline, 12 and 24 weeks. Evaluations were made of patient weight loss, practitioner willingness to utilize available weight loss interventions, practitioner set weight loss goals and the appropriateness of such goals. Overall, the 57% of completing patients lost an average of 6.1% ± 0.5% body weight, with 27.2% losing ≥10% body weight. Practitioners were hesitant to intensify treatment, and those with comorbidities were less likely (odds ratio 1.8; 95% CI 1.4–2.4) to receive intensified treatment than those without. Practitioners also tended to set high weight loss goals, with a mean goal of 17.3% body‐weight loss. The clinically significant mean weight loss demonstrates that practitioners are able to generate meaningful weight loss in primary care settings, however, could benefit from increased use of available interventions.